2010
DOI: 10.1021/nl101281a
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Control of Plasmonic Emission Enhancement from Quantum Dots near Single Silver Nanoprisms

Abstract: The near-field effects of plasmonic optical antennas are being explored in applications ranging from biosensors to solar cells. We demonstrate that photoluminescence emission enhancement from CdSe quantum dots (QDs) can be obtained in the absence of any excitation enhancement near single silver nanoprisms. The spectral dependence of the radiative and nonradiative decay rate of the QDs closely follows the silver nanoparticle plasmon scattering spectrum. Using both experiment and theory we show that, in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
246
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(261 citation statements)
references
References 44 publications
10
246
1
1
Order By: Relevance
“…This non-radiative rate enhancement can be explained by the increased spectral overlap between the fluorescence of the emitter and the absorption of the metal, leading to more efficient energy transfer to the gold. 37,38 To explore these findings further we performed finitedifference time-domain simulations 26 of the antenna-emitter system (FDTD Solutions, Lumerical). The LH2 with its 27 BChl is modeled as a single point dipole source.…”
Section: Resonant Enhancement Of the Radiative And Non-radiative Decamentioning
confidence: 99%
See 1 more Smart Citation
“…This non-radiative rate enhancement can be explained by the increased spectral overlap between the fluorescence of the emitter and the absorption of the metal, leading to more efficient energy transfer to the gold. 37,38 To explore these findings further we performed finitedifference time-domain simulations 26 of the antenna-emitter system (FDTD Solutions, Lumerical). The LH2 with its 27 BChl is modeled as a single point dipole source.…”
Section: Resonant Enhancement Of the Radiative And Non-radiative Decamentioning
confidence: 99%
“…In general, for simpler fluorophores, only a few experimental studies have investigated this 14,35,36 and quantified the specific contribution of the radiative and non-radiative decay rate enhancement. 25,37,38 Here, we report the complete characterization (polarization, spectra and lifetime) of the enhanced emission of light-harvesting complex 2 (LH2) from purple photosynthetic bacteria when coupled to a gold nanorod antenna. Antennae of increasing lengths were used to investigate how the resonance wavelength affects these properties.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [148] reported excitation enhancement of CdSe quantum dots by single metal nanoparticles, whereas emission enhancement of CdSe quantum dots due to silver nanoprisms has been observed by Munechika et al [149]. Enhancement of upconversion emission in NaYF 4 :Er, Yb by silver nanowires [150] and gold nanospheres [151] has been observed.…”
Section: Plasmon-enhanced Fluorescence In Nanoparticlesmentioning
confidence: 96%
“…3 that metal nanostructures (i.e., plasmonics substrates) can efficiently collect light and enhance the intensity due to surface plasmon resonances (SPR). These effects have been widely used for enhancing various optical processes, such as Raman scattering and downconversion luminescence [141][142][143][144][145]. So, in this section, we focus on the fabrication of UCNPs-metal nanocomposites, which is an important way to enhance the upconversion luminescence according to the SPR effect of metals [146][147][148][149][150][151][152].…”
Section: Ucnps-metalsmentioning
confidence: 99%